(untitled) (Journal of Comparative & International Higher Education, 2022)
The world has witnessed democratic decline in 23 countries worldwide during the last decade (Freedom House, 2019) in the context of rising nationalism and right-wing populism (Fraser, 2017; Robertson, 2018, 2020). The political importance of this topic is rooted in the fact that higher education is one of the most crucial public goods (Marginson, 2007, 2017) and governments tend to exercise tighter control over HEIs while democratic conditions worsening (Perry, 2015). Although many studies have examined the effects of the transition to democracy on higher education globally (O’Donnell et al., 2013; O’Donnell et al., 1986, Salto, 2020), very few have studied the reverse trend – democratic backsliding. Given that university autonomy is a wider term that encompasses the practises undertaken by universities to operate, researching its aspects, and assessing the true implications of democratic backsliding on universities represents an important field for current and future research. My research investigates the impact of democratic backsliding on the university autonomy, by examining the cases of Turkey, Hungary, and Poland. These countries were considered democracies until the 2010s, but they are increasingly moving away from democracy (Freedom House, 2020). The study draws on an extensive analysis of publicly accessible government laws and regulations, university decrees, mission statements, political pamphlets, online media sources and interviews, and grey literature to analyze institutional responses as well as field work and interviews. I employ neoliberal authoritarianism and historical institutionalism as a framework to investigate the critical junctures and institutional changes affecting appointive (hiring, promotion, and dismissal of staff), financial (funding levels and criteria, preparation and allocation of the university budget, and accountability), and academic (access, curriculum, degree requirements, and academic freedom) autonomy (Ordorika, 2003).